Prevalência das infecções cutâneas fúngicas em transplantados renais atendidos em hospital da Grande Vitória, ES - Ferreira, Priscila Ventorim Lisboa (2013)
Introduction: Several cutaneous changes have been reported in renal transplant recipients, most of them due to immunosuppressive effects or side effects of the drugs and can be grouped into viral, bacterial and fungal infections, pre-neoplastic and neoplastic, and iatrogenic. Objectives: 1 - Determine the etiologic agents and clinical forms of mycoses observed in renal transplant recipients studied. 2 - Correlate the occurrence of fungal infection with immunosuppressive regimen and time of transplantation. 3 - Evaluate the frequency of bacterial and viral skin diseases. Materials and Methods: Descriptive cross-sectional study with convenience sampling, which evaluated 82 renal transplant recipients under immunosuppressive medications, treated at a hospital in Vitória (ES) in the years 2011 and 2012. After dermatological examination, skin scrapings were performed by light microscopy and mycological culture. Results: The sample consisted mostly of males and a mean age of 49.2 years. The most frequent regimen was the combination of Prednisone + Tacrolimus + Mycophenolate sodium (46.3%) and it was the most related to dermatomycoses. The frequency of dermatomycoses was 28%, with 19.5% of onychomycosis, 6.1% of pitiryasis versicolor and 2.4% of Tineas. We also found 7.3% of common warts, 2.4% of herpes simplex and the same percentage of 1.22% for molluscum contagiosum, erysipelas and furunculosis. The group of patients with late transplant (between 3 and 5 years) showed the highest frequency of dermatomycoses. Conclusions: The clinical aspects of dermatomycoses was similar but it was more frequent than that observed in the general population. The percentage of cutaneous infections was similar to that of immunocompetent population.